Transforming Employee Performance with AppSheet I-DO Digital Product Knowledge Enhancement - Angga Pratama (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to explore the contribution of the AppSheet I-DO application in improving product knowledge and employee performance, especially the role of Nivea Hansaplast Consultant and Beiersdorf Merchandiser. With an exploratory qualitative-descriptive approach, this study involved 11 informants through in-depth interviews, participant observation, and documentation. The results showed that the Interactive Development Environment Application significantly improved training efficiency, product understanding, and confidence in product communication. Flexibility of access, ease of navigation, and prototyping approach made the Interactive Development Environment easily accepted and relevant to the needs of frontliners. The positive impact was seen from the achievement of sales targets above 100% and consistent customer data improvement. The implementation of I-DO reflects a digital socio-technological transformation model that aligns technology, management, and users. This application functions as an educational tool as well as a strategic platform for making data-based decisions, increasing individual accountability and collective performance. These findings are the importance of digitalization in strengthening human resource capabilities and organizational competitiveness. This study provides a basis for developing application-based digital training strategies in other work sectors, to encourage organizational adaptability and excellence in facing the dynamics of the digital industry.